PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS V SD NEGERI 060942 MEDAN DELI - Lumban Gaol, Karunia Novelina; Anton Sitepu; Joen Parningotan Purba; Patri Janson Silaban; Frikson Jony Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the Effect of the Quantum Teaching Learning Model on Student Learning Outcomes in Mathematics Subjects at Elementary School 060942 Medan Deli in the 2024/2025 Academic Year. The independent variable in this study is the Quantum Teaching Model (X) and the dependent variable is Learning Outcomes (Y). Sampling using Saturated Sampling where the population used as a sample is 30 students of grade V of Elementary School 060942 Medan Deli. To determine the initial abilities of students, the researcher conducted a Pretest with an average value of 42.80 with the category of needing guidance. After the study using the Quantum Teaching learning model showed that student learning outcomes increased against the posttest with an average value of 81.87 with a good category. The magnitude of the influence of the Quantum Teaching learning model on student learning outcomes in Mathematics subjects in grade V of Elementary School 060942 Medan Deli was obtained from the results of the correlation test calculation obtained by 0.803 with a very strong category, which means r count (0.803) ≥ r table (0.361). Furthermore, hypothesis testing (t-test) where t count ≥ t table is 7.141 ≥ 1.697 so that it can be stated that Ha is accepted and Ho is rejected. This shows that there is an influence of the Quantum Teaching learning model on student learning outcomes in Mathematics lessons in class V of SD Negeri 060942 Medan Deli.